Toward a Sustainable Palette: Scientific Insights into Natural Pigments and Binders for Environmentally Conscious Art Practices - Kusumadewi, Kenya Permata; Putri, Trikaloka Handayani (Indonesian Scientific Publication, 2025)
The use of synthetic paints in fine art has raised growing environmental concerns, particularly regarding volatile organic compound (VOC) emissions and microplastic pollution. This study investigates the potential of natural pigments and biodegradable binders to serve as sustainable alternatives. It aims to assess their performance through standardized testing of lightfastness, binder compatibility, and environmental impact. A range of mineral pigments (e.g., ochres, sienna, green earth) and botanical lake pigments (e.g., madder, indigo, turmeric) were combined with solvent free binders such as gum arabic, egg tempera, and linseed/walnut oil. Botanical lakes were prepared using alum based precipitation methods. Paint samples were applied to cotton paper and mineral gesso panels, followed by lightfastness testing using ISO Blue Wool standards and ΔE* measurements. Environmental metrics including energy consumption, waste output, and microplastic risk were evaluated using a simplified life cycle inventory (LCIA) framework. The results showed that mineral pigments delivered excellent durability (Blue Wool 7–8), while botanical lakes varied in stability. Madder and indigo were moderately stable, whereas turmeric was highly fugitive (Blue Wool 1–2). Gum arabic and egg tempera demonstrated superior ecological profiles, with zero VOC emissions and high biodegradability. Linseed and walnut oils offered good artistic performance but required careful storage. All tested combinations avoided microplastic generation. These findings confirm that a select range of natural pigment and binder combinations can meet both artistic and environmental standards. The study supports the integration of sustainable materials into fine art practices and provides a model for future research and institutional policy development focused on eco conscious art production.